Electrochemical corrosion study of La(Fe11, 6-xSix1, 4Mnx)H1, 5 in diverse chemical environments. (1st December 2022) - Rocabert, Ulysse; Muench, Falk; Fries, Maximilian; Beckmann, Benedikt; Loewe, Konrad; Vieyra, Hugo A.; Katter, Matthias; Barcza, Alexander; Ensinger, Wolfgang; Gutfleisch, Oliver
Highlights: linear sweep voltammetry of La-Fe-Si alloys, focusing on La(FeMnSi)13 H1, 5 electrolytes: citrate, carbonate and TRIS buffers, NaCl and NaOH solutions impact of commercial corrosion inhibitors and defined protective compounds assessment of protection strategies for operation in magnetocaloric cooling Abstract: La-Fe-Si-based alloys represent a promising material class for magnetocaloric cooling at ambient temperatures, but contain highly oxophilic elements and are chemically sensitive, which impairs their continued operation in aqueous heat exchange media. The development of protection strategies ensuring long-term stability necessitates a comprehensive understanding of the material's corrosion characteristics. The present work focuses on a such an assessment for hydrogenated La(FeMnSi)13 containing α-Fe to enhance it's mechanical properties. Linear sweep voltammetry served as the main analytical tool and was performed in preferably buffered electrolytes with pH values reaching from moderately acidic to strongly alkaline, in the presence and absence of corrosion-enhancing species (chloride, chelators). α-Fe, La1 Fe1 Si1, and La(FeSi)13 were employed as reference materials to clarify the passivation pattern of the material in carbonate buffer. Specific chemical compounds with clear mechanistic impact (phosphate acting as precipitate former, hydrazine as oxygen scavenger) were tested alongside commercial corrosion inhibitors to investigate their effects. Our objective is to provide a systematic evaluation of the corrosion properties of the alloy system, building on previous investigations and taking into account its general materials chemistry. Graphical abstract: Image, graphical abstract